Obstacles for biology education students in the process of implementing online learning at Labuhanbatu University during the covid-19 pandemic - Adek Tiya Pratiwi; Risma Delima Harahap (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The aim of this research is to identify and analyze the obstacles that biology education students at Labuhanbatu University face when implementing online learning during the COVID-19 pandemic. This study employs a descriptive method in conjunction with a qualitative approach. The approach taken is one of survey. This study collected data using data trigulation techniques. The respondents were 92 students enrolled in the Labuhanbatu University biology education study program throughout the academic years 2018/2019; 2019/2020; and 2020/2021. The online learning process is implemented in the following indocators: readiness and implementation in online learning is 87.21%, (physical, psychological) health in online learning is 76.59%, the obstacles faced by the students during online learning process is 72.06%, internet access facilities (quotas) and learning tools in online learning is 79.89%, lecturer services and delivery of materials in online learning is 77.60%, motivation and comprehension of course material development in online learning is 68.76%. Learning motivation and understanding obstacles encountered by biology education students throughout the implementation process might render online learning ineffective, resulting in this research is planned to serve as a benchmark for future improvements in the process of integrating online learning.Abstrak Tujuan dari penelitian ini adalah Untuk mengetahui dan menganalisis hambatan apa saja yang dihadapi mahasiswa pendidikan biologi Universitas Labuhanbatu dalam pelaksaanaan proses pembelajaran daring di masa pandemi COVID-19. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pendekatan yang digunakan adalah pendekatan survey. Teknik pengumpulan data dalam penelitian ini menggunakan teknik trigulasi data,Responden adalah mahasiswa program studi pendidikan biologi Universitas Labuhanbatu angkatan tahun akademik 2018/2019: 2019/2020;2020/2021,dengan jumlah total sebanyak 92 orang.Hasil penelitian ini menunjukkan beberapa hambatan mahasiswa dalam pelaksanaan proses pembelajaran daring diantaranya yaitu :Kesiapan dan pelaksanaan dalam pembelajara daring 87,21%, Kesehatan (fisik,psikis) dalam pembelajaran daring 76,59%, Hambatan yang dialami mahasiswa selama proses pembelajaran daring 72,06%, Fasilitas akses internet (kuota) dan perangkat pembelajaran dalam pembelajaran daring 79,89%, Pelayanan dosen dan penyampaian materi dalam pembelajaran daring 77,60%, Motivasi pembelajaran dan memahami materi perkuliahan dalam pembelajaran daring 68,76%, Hamabatan yang dialami oleh para mahasiswa pendidikan biologi dalam pelaksanaan proses pembelajaran daring akan membuat pembelajaran daring menjadi tidak maksimal, sehingga penelitian ini diharapkan menjadi evaluasi sebagai acuan perbaikan didalam proses pelaksanaan pembelajaran daring menjadi baik kedepannya.